Back to the future: rethinking socioecological systems underlying high nature value farmlands. Issue 1 (9th December 2019) - Lomba, Angela; Moreira, Francisco; Klimek, Sebastian; Jongman, Robert HG; Sullivan, Caroline; Moran, James; Poux, Xavier; Honrado, João P; Pinto‐Correia, Teresa; Plieninger, Tobias; McCracken, David I
Abstract : Farmlands are currently among the dominant uses of the land. When managed under low‐input farming systems, farmlands are associated with diverse cultural and natural heritages around the world. Known in Europe as high nature value (HNV) farmlands, these agricultural landscapes and their associated farming systems evolved as tightly coupled socioecological systems, and are essential to biodiversity conservation and the delivery of ecosystem services to society. However, HNV farmlands are vulnerable to socioeconomic changes that lead to either agricultural intensification or land abandonment. We present a range of plausible future scenarios for HNV farmlands, and discuss the related management options and expected socioecological outcomes for each scenario. We then provide recommendations for policy, practice, and research on how to best ensure the socioecological viability of HNV farming systems in the future.